2012
DOI: 10.5392/ijoc.2012.8.1.074
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic Effects of Transcranial Direct Current Stimulation on Central Neuropathic Pain in Spinal Cord Contusive Rat Model

Abstract: The aim is to investigate the analgesic effect of transcranial direct current stimulation(tDCS) on central neuropathic pain(CNP) in spinal cord contusive rat model. Twenty Sprague-Dawley rats (250±50 g, male) were used. Thoracic spinal cord(T10) A central neuropathic pain caused by a spinal cord injury may be divided into a nociceptive pain by over-activity of peripheral sensitization receptor and a neuropathic pain by nerve damage.They act as the limit of several physiotherapies because they cause heavy pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
(43 reference statements)
0
2
0
Order By: Relevance
“…Recently, transcranial direct current stimulation (tDCS) has been used as a central neurostimulation technique, as it has been presented as an effective and safe noninvasive brain stimulation method (Kim et al 2012). tDCS releases a weak current to the scalp and selectively triggers changes in neuron excitation in the local brain regions (Nitsche and Paulus 2000;Liebetanz et al 2002), it affects the activity of sodium and calcium ion channels, adjusting the potential level of the neural network, and changes the activity of the local brain neurons in the relevant region (Nitsche and Paulus 2000;Liebetanz et al 2002;Nitsche et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, transcranial direct current stimulation (tDCS) has been used as a central neurostimulation technique, as it has been presented as an effective and safe noninvasive brain stimulation method (Kim et al 2012). tDCS releases a weak current to the scalp and selectively triggers changes in neuron excitation in the local brain regions (Nitsche and Paulus 2000;Liebetanz et al 2002), it affects the activity of sodium and calcium ion channels, adjusting the potential level of the neural network, and changes the activity of the local brain neurons in the relevant region (Nitsche and Paulus 2000;Liebetanz et al 2002;Nitsche et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a number of studies have investigated the impact of non-invasive brain stimulation (NIBS) on the enhancement of neuroplasticity and the recovery of symptoms caused by brain lesions ( Hummel and Cohen, 2006 ; Summers et al, 2007 ; Kim et al, 2016 ; Satow et al, 2016 ; Andrade et al, 2017 ). Transcranial direct current stimulation (tDCS) is a NIBS technique that uses low-intensity direct current to modulate the excitability of neurons in different cortical sections and deep areas of the brain ( Nitsche and Paulus, 2000 ; Liebetanz et al, 2002 ; Kim et al, 2012 ). Previous studies have suggested that the application of tDCS to the primary motor cortex (M1) can improve upper limb motor function.…”
Section: Introductionmentioning
confidence: 99%